Unraveling the Bioactive Potential of Camellia japonica Edible Flowers: Profiling Antioxidant Substances and In Vitro Bioactivity Assessment - Antia G. Pereira; Maria Fraga-Corral; Aurora Silva; Maria Fatima Barroso; Clara Grosso; Maria Carpena; Pascual Garcia-Perez; Rosa Perez-Gregorio; Lucia Cassani; Jesus Simal-Gandara; Miguel A. Prieto (MDPI AG, 2024)
In recent years, the search for novel natural-based ingredients by food and related industries has sparked extensive research aimed at discovering new sources of functional molecules. Camellia japonica, traditionally known as an ornamental plant, has gained attention due to its diverse array of bioactive compounds with potential industrial applications. Although C. japonica flowers are edible, their phytochemical profile has not been thoroughly investigated. In this study, a phenolic profile screening through an HPLC-ESI-QQQ-MS/MS approach was applied to C. japonica flower extracts, revealing a total of 36 compounds, including anthocyanins, curcuminoids, dihydrochalcones, dihydroflavonols, flavonols, flavones, hydroxybenzoic acids, hydroxycinnamic acids, isoflavonoids, stilbenes, and tyrosols. Following extract profiling, their bioactivity was assessed by means of in vitro antioxidant, antimicrobial, cytotoxic, and neuroprotective activities. The results showed a multifaceted high correlation of phenolic compounds with all the tested bioactivities according to Pearson's correlation analysis, unraveling the potential of C. japonica flowers as promising sources of nutraceuticals. Overall, these findings provide insight into the valorization of C. japonica flowers from different unexplored cultivars thus diversifying their industrial outcome.